FlexFT: A Generic Framework for Developing Fault-Tolerant Applications in the Sensor Web - Delano Medeiros Beder; Jó Ueyama; João Porto de Albuquerque; Marcos Lordello Chaim (International Journal of Distributed Sensor Networks)
Fault-tolerant systems are expected to operate in a variety of devices ranging from standard PCs to embedded devices. In addition, the emergence of new software technologies has required these applications to meet the needs of heterogeneous software platforms. However, the existing approaches to build fault-tolerant systems are often targeted at a particular platform and software technology. The objective of this paper is to discuss the use of F l e x F T —a generic component-based framework for the construction of adaptive fault-tolerant systems that can integrate and reuse technologies and deploy them across heterogeneous devices. Furthermore, F l e x F T provides a standardized and interoperable interface for sensor observations by relying upon the “Sensor Web” paradigm established by the Open Geospatial Consortium (OGC). We have implemented a Java prototype of our framework and evaluated the potential benefits by carrying out case studies and performance measurements. By implementing and deploying these case studies in standard PCs as well as in sensor nodes, we show that F l e x F T can cope with the problem of a wide degree of heterogeneity with minimal resource overheads.